1999
DOI: 10.1212/wnl.53.5.1012
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-release and controlled-release carbidopa/levodopa in PD

Abstract: Despite the progressive nature of PD, both the immediate-release and sustained-release carbidopa/levodopa formulations maintained a similar level of control in PD after 5 years compared with baseline. Additionally, the low incidence of motor fluctuations or dyskinesia was not significantly different between the treatment groups and may be partly attributed to the relatively low doses of levodopa used throughout the 5-year study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(104 citation statements)
references
References 19 publications
3
96
0
5
Order By: Relevance
“…These studies demonstrated no difference in the incidence in dykinesias and motor fluctuations with the CR formulation [31][32][33][34]. The intestinal absorption of carbidopa-levodopa-CR is incomplete and variable.…”
Section: Controlled-release Levodopa and Catechol-omethyltransferase Inmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies demonstrated no difference in the incidence in dykinesias and motor fluctuations with the CR formulation [31][32][33][34]. The intestinal absorption of carbidopa-levodopa-CR is incomplete and variable.…”
Section: Controlled-release Levodopa and Catechol-omethyltransferase Inmentioning
confidence: 92%
“…As previously discussed, the CR formulation of levodopa is variably absorbed, the time to effect is delayed and the duration of clinical benefit is only mildly extended [30][31][32]. Recently, the investigational drug IPX066 has emerged as a novel ER formulation.…”
Section: Novel Er Formulation Of Oral Carbidopa-levodopa: Ipx066mentioning
confidence: 99%
“…Despite the initial success in relieving the motor symptoms, pharmacological interventions have limited therapeutic benefit as the disease progresses, which can be attributed to the fact that clinical symptoms emerge when as much as 60-80% of the nigral DA neurons are lost (104,228). Thus, the beneficial effects wear off after 4-6 years of treatment, leading to development of motor fluctuations (increased parkinsonian symptoms when the medication effect ends) and dyskinesias (drug-induced involuntary movements) (229,230).…”
Section: Current Treatmentmentioning
confidence: 99%
“…24 Stunden durchgeführte LevodopaPlasmaspiegelprofile zeigten nach Gabe von retardierten LevodopaPräparaten gleichmäßigere Levodopa-Plasmakonzentrationen im Gegensatz zu denen nach Einnahme von Standardformulierungen (15,28,35,36). Allerdings wiesen bisherige Langzeitstudien, die normale und retardierte Levodopa-Formulierungen hinsichtlich der Manifestation von Fluktuationen und Dyskinesien bei zuvor unbehandelten Parkinsonpatienten verglichen, keine signifikanten Unterschiede fünf Jahre nach Ersteinstellung auf Levodopa auf (37,38).…”
Section: Designunclassified
“…In dieser Studie erhielten die Patienten durchschnittlich 728 mg retardiertes Levodopa/Carbidopa oder 510 mg der Standardformulierung (38). Eine ähnliche Untersuchung mit retardierten Levodopa/ Benserazid-Präparaten fand ebenfalls keine signifikanten Unterschiede hinsichtlich der Manifestation von motorischen Komplikationen.…”
Section: Designunclassified